Diverse Host-Seeking Behaviors of Skin-Penetrating Nematodes - Castelletto, Michelle L. (Public Library of Science, 2014)
Skin-penetrating parasitic nematodes infect approximately one billion people worldwide and are responsible for some of the most common neglected tropical diseases. The infective larvae of skin-penetrating nematodes are thought to search for hosts using sensory cues, yet their host-seeking behavior is poorly understood. We conducted an in-depth analysis of host seeking in the skin-penetrating human parasite Strongyloides stercoralis, and compared its behavior to that of other parasitic nematodes. We found that Str. stercoralis is highly mobile relative to other parasitic nematodes and uses a cruising strategy for finding hosts. Str. stercoralis shows robust attraction to a diverse array of human skin and sweat odorants, most of which are known mosquito attractants. Olfactory preferences of Str. stercoralis vary across life stages, suggesting a mechanism by which host seeking is limited to infective larvae. A comparison of odor-driven behavior in Str. stercoralis and six other nematode species revealed that parasite olfactory preferences reflect host specificity rather than phylogeny, suggesting an important role for olfaction in host selection. Our results may enable the development of new strategies for combating harmful nematode infections.